Synthesis of nanocomposites by in situ metallocene-catalyzed polymerization of propene - Zakrzewska, S.; Dos Ouros, A. C.; Schramm, N.; Jehnichen, D.; Haeussler, L.; Pospiech, Doris; Voit, Brigitte; Schulze, U.; Pastore, H. O. (European Polymer Journal, 2015)
Organo-modified aluminophosphate with kanemite-like structure was used for the in situ synthesis of polypropylene (PP) nanocomposites performed by metallocene-catalyzed polymerization. The filler exhibits a layered structure with different organic pending groups arranged in the interlayer space. Melt-compounded composites with the same filler were prepared for comparison. X-ray diffraction (XRD) and transmission electron microscopy (TEM) proved exfoliation of the filler in the PP matrix and formation of nanocomposite after in situ synthesis. In contrast, in the melt-composites the filler is agglomerated and only microcomposites are obtained.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Aluminophosphate; Kanemite structure; Metallocene; Nanocomposites; Polyolefins